“Evaluation Of Training Programme Of Punjab Dairy Development Department” - Kumar, Dinesh; Sahota, R.S.; Verma, H.K.; Kasrija, Rajesh; Kansal, S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted on 120 trainees of Punjab Dairy Development department at different dairy training centers viz. Phagwara, Sardulgarh, Bija, Chatamli and Tarantaran, to evaluate the training programmes with the help of pre-structured and pre-tested knowledge test. There is an appreciable increase in the knowledge of the trainees in sub areas like housing, feeding, health aspect, breeding and general information after the training and the training course significantly improved the knowledge score of trainees after the completion of the course.
Keywords: Evaluation; Training Programme